SME’s Perspective on Psychosocial Risks – From identifying to intervening in four countries - Costa, P.; Ramos, S.; Silva, S.A.; Passos, A. M.; Tavares, S. M.; Bretones, F. D.; Delgado, A.; Doulougeri, K.; Georganta, K.; Giacominelli, B.; González, J. M.; González, R.; et al. (12th EAOHP Conference (“Occupational health psychology in times of change: society and the workplace”)., 2016)
Introduction: Certain aspects of the work design or the organization as well as the social context of work may lead to negative physical, psychological and social outcomes. These aspects are considered psychosocial risks. Portugal, Spain, Italy, and Greece are facing the biggest consequences of the economic crisis with psychosocial risks being exacerbated. In these countries, small and medium enterprises play an important role in the economy. This paper presents the quantitative data from the project, collected in those four countries. The main goal of the survey was to determine the SMEs’ perspective about emergent psychosocial risks, difficulties and concerns related to its prevention as well as to assess their knowledge and existing practices regarding psychosocial risks prevention. Methodology: The survey was developed based on existing surveys for assessing psychosocial risks, as well as on data gathered in the qualitative phase of the project (consisting in interviews with key stakeholders). It was accessible either in an online format or as a paper copy. In total, 154 SME safety and health technicians and workers representatives participated in the study. Results: Although being an important issue, specific policies, management systems, or action plans on psychosocial risks are rarely found in SMEs. Also, risk assessment is seldom conducted, as it is considered too expensive and time consuming. When risk assessment is conducted, it is usually to comply with legal requirements or requirements from clients as well as over concern about the organization's reputation. In general, participants agree that they need more information to promote risk assessment. Discussion: While health and safety is already an integral part of the management philosophy in most SME’s, the introduction of preventive actions beyond legal requirements still need improvement. The project revealed a low level of awareness about psychosocial risks, the almost inexistence of risk assessment practices and a lack of resources for investing in its prevention. To facilitate the change in the prevention practices it is critical to develop resources that organizations could easily use at a low cost.